Penyelesaian Sengketa Pembiayaan Dengan Objek Jaminan Hak Tanggungan Pada Bank Syariah Di Kota Malang - Nur Islamiyah Puspasari; Novilia Safitri Dewik; Sinta Amipatul Aisiyah; Nur Putri Hidayah (Universitas Muhammadiyah Sumatera Utara, 2020)
In financial agreement, a bank as creditor has the authority to ask a client as debtor to place a guarantee such as a mortgage guarantee based on the Article 8 of Banking Regulation. Based on the Article 20 of Law of Mortgage, the availability of mortgage guarantee enables the bank to execute the object of guarantee when the debtor is in default. However, a concrete regulation concerning on the resolution procedure of banking dispute has not been stipulated. The only reference for this issue is the Regulation of OJK (Financial Service Authority) Number 1/POJK/.07/2014 pertaining to the Alternative Institution for Dispute Resolution in Financial Service Sector (POJKLAPS). The problem is, the institution only exists in Jakarta. In fact, there are many cases where the debtors considered themselves as the victim of banking crime due to unclear procedure of the execution of the object of guarantee. This study aimed to investigate the procedure of financial dispute resolution with the object of mortgage guarantee in sharia banks in Malang City and to figure out the constraints encountered during the process.